An Overview of the Contents & Manners of Quranic Text - Sumbal Ashraf; Sadaf Sultan (jihat-ul-islam, 2022)
The Quran is an ultimate miracle. The greatest miracle that Allaah SWT has given to the Prophet (peace be upon him) is this Qur'an. Allah SWT blessed every Prophet with the miracles; He blessed them with the miracles according to the situations, needs and the temperament of the people of that particular era. In the reign of Hazrat Muhammad SAW, there was a period of rhetoric and oratory among Arabs. They used to find themselves on top in this field. And to a larger extent this was true. Therefore, the Almighty revealed a miracle of the Qur’an, which is, in itself, a masterpiece of eloquence and oratory. This book invites the audience to the religion in every way possible. It is a complete guide in every attribute whether its research approach, academic methodology, rational technique, writing, inspirational manner and scientific appeal. In any way, it calls for goodness and righteousness. The Qur'an has infinite and numerous unique properties, which are not possible to be covered fully. It has unprecedented principles and manners for transmission of its message to the remembrance by humanity.